A double-blind controlled trial of the effect of sodium cromoglycate in preventing relapse in ulcerative colitis. Issue 669 (July 1981) - Whorwell, P. J.; Whorwell, G. M.; Bamforth, J.; Colin Jones, D.; Down, P.; Edwards, A.; Gent, A. E.; Golding, P.; Gough, K. R.; Hellier, M. D.; Isaacson, P.; Loehry, C. A.; et al.
Abstract : A double-blind controlled trial of the effect of sodium cromoglycate (SCG) in preventing relapse in ulcerative colitis has been completed in 100 subjects. In patients already taking sulphasalazine, SCG did not prove to be of any additional benefit. However, in patients not on any other maintenance therapy, the relapse rate was 40% for SCG as compared with 75% for placebo. A large study of the effect of SCG in patients intolerant of sulphasalazine is indicated.